MEASLES WITH THE COMPLICATION OF NON-OBSTRUCTIVE HYPERTROPHIC CARDIOMYOPATHY; CASE REPORT - Ramna Shafique Rafique; Saleha Haider; Maria Kanwal; Saba Safdar; Tayyaba Anwar; Zain Yousaf Ally (Baqai Journal of Health Sciences)
Measles is a highly contagious disease caused by a viral infection. It is transmitted through the respiratory route, and the illness begins with fever, cough, coryza, and conjunctivitis, followed by a distinctive rash. It is best prevented through vaccination. Complications that can be seen in measles are otitis media, diarrhea, pneumonia, encephalitis, and myocarditis, and a long-term complication is subacute sclerosing panencephalitis. We present a case of a 6-month-old girl who came with measles-like symptoms and later developed complications of non-obstructive hypertrophic cardiomyopathy.